Close Encounters of Lymphoid Cells and Bacteria - Cruz-Adalia, Aranzazu; Veiga, Esteban (Frontiers in Immunology, 2016)
During infections, the first reaction of the host against microbial pathogens is carried out by innate immune cells, which recognize conserved structures on pathogens, called pathogen-associated molecular patterns (PAMPs). Afterwards, some of these innate cells can phagocytose and destroy the pathogens, secreting cytokines that would modulate the immune response to the challenge. This rapid response is normally followed by the adaptive immunity, more specific, and essential for a complete pathogen clearance in many cases. Some innate immune cells, usually named antigen presenting cells (APCs), like macrophages or dendritic cells, are able to process internalized invaders and present their antigens to lymphocytes, triggering the adaptive immune response. Nevertheless, the traditional boundary of separated roles between innate and adaptive immunity has been blurred by several studies, showing that very specialized populations of lymphocytes (cells of the adaptive immunity), behave similarly to cells of the innate immunity. These “innate-like” lymphocytes include γδ T cells, invariant NKT cells, B-1 cells, mucosal associated invariant T (MAIT), marginal zone B cells (MZ B cells), innate response activator (IRA) cells and together with the newly described innate lymphoid cells (ILCs), are able to rapidly respond to bacterial infections. Strikingly, our recent data suggest that conventional CD4+ T cells, the paradigm of cells of the adaptive immunity, also present innate-like behavior, capturing bacteria in a process called transinfection. Transinfected CD4+ T cells digest internalized bacteria like professional phagocytes and secrete large amounts of pro-inflammatory cytokines, protecting for further bacterial challenges. In the present review, we will focus on the data showing such innate-like behavior of lymphocytes following bacteria encounter.